Chapter 6 Problem-based Learning in International Online Groups - Creelman, Alastair (Taylor & Francis, 2021)
Open Networked Learning is an open online professional development course for educators in higher education who wish to investigate and discuss the design and teaching of collaborative online courses. The course is organised in a unique partnership between 14 institutions in six countries and is both an institutional professional development course and an arena for virtual exchange between educators from different cultures, institutions and disciplines. This chapter describes how the course successfully implements problem-based learning in facilitated groups in an online environment. The course employs a multi-layered approach to openness and allows learners to participate on three levels: as part of the course community, within the problem-based learning group and with individual reflection in a learning blog. This chapter examines the opportunities and challenges that have arisen and points to possible solutions.